2020
DOI: 10.3389/fonc.2020.598579
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Ovarian and Uterine Clear Cell Malignancies

Abstract: PurposeOvarian and uterine clear cell carcinomas (CCCs) are rare but associated with poor prognosis. This study explored RNA transcription patterns characteristic of these tumors.Experimental DesignRNA sequencing (RNA-seq) of 11 ovarian CCCs and five uterine CCCs was performed and compared to publicly available data from high grade serous ovarian cancers (HGSOCs). Ingenuity Pathway Analyses were performed. CIBERSORT analyses estimated relative fractions of 22 immune cell types in each RNA-seq sample. Sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Pooled analysis was performed using the Audic-Claverie (AC) test, which pools together raw counts across three sets of vitamin-C-treated and untreated BEAS-2B cells, separately, and tests the differences between them based on a Poisson assumption of the distribution of counts. A multiple testing correction, Benjamini-Hochberg FDR (false discovery rate) of 0.05, and a maximum p-value cutoff of 0.05 were used as described previously [14,17]. The genes of the AC test were ranked based on adjusted p-value (FDR corrected), and cutoff was set at p adj < 0.05 to select for statistically significant differentially expressed genes between the vitamin-C-treated and untreated BEAS-2B cells.…”
Section: Rna Sequencing and Analysismentioning
confidence: 99%
“…Pooled analysis was performed using the Audic-Claverie (AC) test, which pools together raw counts across three sets of vitamin-C-treated and untreated BEAS-2B cells, separately, and tests the differences between them based on a Poisson assumption of the distribution of counts. A multiple testing correction, Benjamini-Hochberg FDR (false discovery rate) of 0.05, and a maximum p-value cutoff of 0.05 were used as described previously [14,17]. The genes of the AC test were ranked based on adjusted p-value (FDR corrected), and cutoff was set at p adj < 0.05 to select for statistically significant differentially expressed genes between the vitamin-C-treated and untreated BEAS-2B cells.…”
Section: Rna Sequencing and Analysismentioning
confidence: 99%
“…RNA quality and quantity were assessed using an Agilent 2100 Bioanalyzer and a Qubit fluorimeter, respectively. All samples exhibited a DV200 metric of over 30% of RNA with fragment sizes over 200 nucleotides, as previously described [52][53][54]. RNA expression profiling Oncotarget 10 www.oncotarget.com was performed using the Illumina Truseq RNA Access library preparation kit.…”
Section: Patients' Characteristics and Rna Sequencing Analysis Of Tas Of Ba And Wa Pca Patientsmentioning
confidence: 99%
“…Several studies have used RNA-Seq to differentiate between OCCC and other cancer types. For example, A previous study exploring differences between OCCC and uterine clear cell carcinomas (UCCC) found that 1607 genes were significantly upregulated and 109 genes were significantly downregulated in OCCC compared to UCCC [52]. Another study by Nagasawa and colleagues employed RNA-sequencing to identify fundamental differences between HGSOC, a common ovarian cancer subtype, with clear cell carcinoma [37].…”
Section: Exploration Of the Rare Ovarian Cancer Transcriptomementioning
confidence: 99%